New cell lines from Ephestia kuehniella: Characterization and susceptibility to baculoviruses - Dwight E. Lynn; Stephen M. Ferkovich (Journal of Insect Science, 2004)
New cell lines from embryos of Ephestia kuehniella were recently developed. Primary cultures were initiated in September 2002 from 2 to 4 day old eggs in either modified TC-100 or Ex-Cell 400 medium. From these initial cultures, one, originally isolated in the Ex-Cell medium, produced sufficient cell growth to allow subcultivation and eventually led to the establishment of two cell strains, one that forms multicellular vesicles in suspension and one consisting of tightly attached epithelial-like cells. The strains were compared to an extract from E. kuehniella eggs by isozyme analysis and shown to be from the same species. Both strains were inoculated with various insect viruses, including nucleopolyhedroviruses from Autographa californica, Anagrapha falcifera, Anticarsa gemmatalis, Galleria mellonella, Heliothis armigera, Helicoverpa zea, Lymantria dispar, Plutella xylostella, and Rachoplusia ou. Both strains were highly susceptible to most of the nucleopolyhedroviruses (with the exception of the viruses from Helicoverpa zea and Lymantria dispar which did not show cytopathology to either cell strain) with large numbers of occlusion bodies produced in most of the inoculated cells. Our results suggest these new lines can be useful in biocontrol research.